KEDUDUKAN LEMBAGA KOMISI PEMBERANTASAN KORUPSI (KPK) DALAM SISTEM KETATANEGARAAN INDONESIA (TELAAH YURIDIS NORMATIF PUTUSAN MK): The Position of the Corruption Eradication Commission (KPK) in the Indonesian Constitutional System (Normative Juridical Review of the Constitutional Court's Decision) - Izzah Qotrun Nada (Constitution Journal, 2022)
The Corruption Eradication Commission (KPK) is an institution established to increase the efficiency and effectiveness of eradicating corruption that has been rampant throughout society. In Law no. 30 of 2002 explains that the KPK is an independent institution and is free from the influence of any power. However, The Corruption Eradication Commission (KPK) is considered by some to be an extra-constitutional institution. The Constitutional Court Decision No. 36/PUU-XV/2017 states that the Corruption Eradication Commission (KPK) is a state institution within the realm of the executive. This decision contradicts the three previous decisions which stated otherwise that the Corruption Eradication Commission (KPK) is an independent state institution through its decision No. 012-016-019/PUU-IV/2006, No. 5/PUU-IX/2011, No. 49/PUU-XI/2013. The KPK has advantages in terms of its duties and authorities which have been regulated in Law no. 30 of 2002 which is now Law Number 19 of 2019 concerning the Corruption Eradication Commission. However, seeing the reality that the public strongly believes in the existence of the KPK, it is unfortunate that the legal politics of eradicating corruption through the establishment of the KPK appears to have no clear legal politics from the government, so that the establishment of the KPK does not set the boundaries of its establishment so that the position of the KPK is currently a polemic. Komisi Pemberantasan Korupsi (KPK) merupakan lembaga yang dibentuk untuk meningkatkan daya guna dan hasil guna terhadap pemberantasan tindak pidana korupsi yang sudah merajalela keseluruh lapisan masyarakat. Dalam UU No. 30 Tahun 2002 menjelaskan bahwa KPK merupakan lembaga independen dan bebas dari pengaruh kekuasaan manapun. Akan tetapi, Komisi Pemberantasan Korupsi (KPK) dianggap oleh sebagian pihak sebagai lembaga ekstrakonstitusional. Putusan Mahkamah Konstitusi No. 36/PUU-XV/2017 menyatakan bahwa Komisi Pemberantasan Korupsi (KPK) merupakan lembaga negara yang berada dalam ranah eksekutif. Putusan tersebut bertentangan dengan tiga putusan sebelumnya yang menyatakan sebaliknya bahwa Komisi Pemberantasan Korupsi (KPK) merupakan lembaga negara independen melalui putusannya No. 012-016- 019/PUU-IV/2006, No. 5/PUU-IX/2011, No. 49/PUU-XI/2013. KPK memiliki kelebihan dalam hal tugas dan wewenangnya yang sudah diatur dalam Undang-undang No. 30 tahun 2002 yang kini menjadi Undang-undang Nomor 19 Tahun 2019 tentang Komisi Pemberantasan Korupsi. Namun melihat realitasnya publik sangat mempercayai adanya KPK, patut disayangkan politik hukum pemberantas korupsi melalui pembentukan KPK tampak tidak ada politik hukum yang jelas dari pemerintah, sehingga pendirian KPK tidak menetapkan batas-batas pendirian sehingga kedudukan KPK menjadi polemik saat ini.